Geographie als Kunst: Zu Herkunft und Kritik eines Gedankens - Hard, Gerhard (ERDKUNDE, 1964)
The concept of geography as creative art and related ideas which put geo graphical work at least into close proximity to artistic work have their original roots in the classical-idealistic epoch of the German movement whence they became part of the classic period of German geography. Within this epoch this was well justified. To speak of geography as a creative art and of the artistic side of geography is not, however, quite beside the point even within the framework of modern geography. True, put as the basic principle of academic study and presentation this concept would be nonsensical, even dangerous. Nevertheless, given its proper place, it could stimulate the study of the literary, belletristic side, especially of early geographical writing which is often overlooked and nearly always underestimated; it would furthermore result in the awareness that even in strictly empirical fields of learning all processes by which knowledge is grouped have inevitably also an artistic and intuitive component.